Solar and stellar magnetic activity - Schrijver, Carolus J. (Cambridge astrophysics series, 2000)
This timely volume provides the first comprehensive review and synthesis of current understanding of magnetic fields in the Sun and similar stars. Magnetic activity results in a wealth of phenomena - including starspots, non-radiatively heated outer atmospheres, activity cycles, deceleration of rotation rates, and even, in close binaries, stellar cannibalism - all of which are covered clearly and authoritatively. This book brings together for the first time recent results in solar studies and stellar studies. The result is an illuminating new view of stellar magnetic activity. Key topics inclu.